Analysis of behaviour patterns and thermal responses to a hot–arid climate in rural China. (July 2016) - Yan, Haiyan; Yang, Liu; Zheng, Wuxing; He, Wenfang; Li, Daoyi
Abstract: Climate can greatly affect building design, life style and thermal perception for all groups of people; however, this phenomenon has not yet been rigorously evaluated in China's hot–arid climate. The aim of this paper is to present the results of a thermal comfort survey by evaluating the influence of the hot–arid climate upon the behavioural patterns and thermal comfort responses of 160 residents in 65 traditional vernacular houses in Turfan, China, in 2011. In this survey, there were 206 sets of effective data, and the features of the traditional residential buildings and the human behaviour patterns in Turfan were described and analysed. The results showed that the diversified courtyards and shade spaces were the most obvious features of traditional houses in Turfan. People here typically spend most of their time in one of two spaces for eating, resting, and entertaining. It was found that the preferred temperature was 26.5 °C. The preferred air velocity occurred at 0.62 m/s. A suitable air velocity range of 0.15–1.24 m/s was suggested in Turfan. Moreover, the neutral temperature of the local people was 30.1 °C (tg or to ). The upper limits of the 80% acceptable zone by using the direct and indirect acceptability method were 32.7 and 33.8 °C, respectively. The neutral temperature and upper limit of the acceptable zone in Turfan were higher than those of the adaptive standards. Attention should be paid to the role of thermal comfort in influencing building design by using simple passive cooling strategies. The above results are believed to be potentially valuable for the design and evaluation of residential buildings located in hot–arid climate. Highlights: The comfort survey performs in a hot–arid climate in rural China. People spend 80% of their time outdoors in summer. The neutral temperature of the occupants is 30.1 °C. The upper limit of the acceptable range is higher than that of the adaptive standards.